Analisis Tingkat Pengangguran Sebagai Masalah Sosial Yang Tak Kunjung Usai - Erwin Dani Setiawan; Fazri Hisyam Mahendra; Niken Seliana Herawatie; Ati Kusmawati (Lembaga Pengembangan Kinerja Dosen, 2024)
Discussion on the issue of unemployment not only focuses on the social aspect but also includes the economic dimension. Unemployment not only presents challenges in the social realm but also influences the economic growth of a country, such as Indonesia. Unemployment refers to the condition when individuals in the workforce desire employment but have not yet achieved it. This research adopts a qualitative approach with data collection conducted through literature reviews, including journals, books, and online sources. Unemployment is a complex problem linked to population growth, economic conditions, government policies, and education levels. It involves aspects of time, labor intensity, and productivity. Unemployment in Indonesia poses a significant problem with economic, employment, and social factors as causes. Its impacts include income reduction, increased poverty, and crime risks. Addressing this requires collaboration between the government, private sector, and society. The government should promote economic growth, enhance education quality, and provide social assistance. Investment in labor-intensive sectors and skills training is also crucial.